The extent of public awareness and use of the Global Solar UV Index as a worldwide health promotion instrument to improve sun protection: A systematic review and meta-analysis - Kaiser, Isabelle; Pfahlberg, Annette; Lehmann, Maria; Buchta, Esther; Uter, Wolfgang; Gefeller, Olaf (Photochemistry and Photobiology, 2025)
Thirty years ago, the Global Solar UV Index (UVI) has been introduced as a health promotion instrument to improve sun protection. We assessed systematically global levels of awareness and use of the UVI as a prerequisite for the preventive effectiveness of this public health tool. We conducted a comprehensive literature search across 10 databases, including PubMed, Scopus and Web of Science Core Collection, as well as clinical trial registries and gray literature databases. The risk of bias of studies was evaluated using the Joanna Briggs Institute checklist for prevalence studies. In addition to narrative and descriptive analysis, we performed meta-analyses with geographical subgroup analyses to statistically summarize the results. In total, we identified 40 publications from 39 different studies across multiple global regions. However, the number of studies in the analyses varies depending on the outcome. The results, especially the awareness of the UVI, were largely dependent on the specific geographical location of the studies. While the prevalence of awareness of the UVI is high among Australian populations, there is considerable variability in levels of awareness across other global regions. At the same time, the use of the UVI is at a low level across all regions, demonstrating the need for enhanced dissemination of knowledge about the perils associated with ultraviolet radiation and the advantages of using the UVI.
CRIS-Team Scopus Importer:2025-02-04
Keywords: awareness; meta-analysis; sun protection; systematic review; use; UV Index